Agri-tourism area development planning in mekarwangi village, sindangkerta sub-district, west Bandung district - Saputro, Lilik Edi; Mezi Julian; Dyah Mustika Wardani; Emmita Devi Hari Putri; Atun Yulianto (SEAN Institute, 2024)
The Government of the Republic Indonesia give opportunities for regional level authorities to develop their regional potential for communal prosperity in. Mekarwangi Village, a designated agricultural area of the village by the Government of West Bandung Regency's Regional and Spatial Planning as well as agritourism through its Engineering Detail Design, has agricultural potential to be developed and managed. This journal provides a model of agritourism development planning through such components as agri tourism activities, facilities, and management for the promotion of Mekarwangi Village as Agri Tourism Area. The outcome of this journal is executive planning by stage, by zone and recommendations based on identification and analysis done previously.